MODEL PEMBELAJARAN BAHASA ARAB BERBASIS TEKNOLOGI - Silviah Noroch; Bambang Hermanto (Institut Kariman Wirayudha Sumenep, 2024)
Learning planning is an important activity that must be planned as thoroughly as possible, especially in the current digital era, including planning learning models to achieve learning goals. As Barry Morris describes learning patterns, the increasing development of knowledge and technology will bring about changes in the role of teachers as messengers. Teachers are not the only learning source in the learning process, but there are many learning resources that students can obtain with the help of technology which is so fast nowadays. This paper uses a qualitative descriptive research approach which is used to investigate, discover, describe and explain a phenomenon. With the conclusion that technology is very helpful in implementing learning, especially learning Arabic. Among the technology-based learning models that can be applied in Arabic language learning are learning models using Moodle, Edmodo and Google Classroom. Keywords: Technology, Arabic language learning model.